The meaning and value of ancient book collections: the library of Francesco Maria II della Rovere - Alfredo Serrai (Bibliothecae.it)
After a reconstruction of the origins and nature of the library of Francesco II Maria della Rovere, the author reflects on the interest and value that such a collection still holds today, especially in light of its completeness and documentary richness.